Decisões gerenciais na implementação do teletrabalho: estudo de caso em uma universidade pública federal - Araújo, Mayra Lima (2024)
Advancements in information technologies have leveraged the delivery of various digital services, which has transformed work practices and facilitated telework. In the Brazilian Federal Public Administration, the first step toward new work arrangements and, consequently, the possibility of telework, was the publication of Decree Nº 1.590 of August 10, 1995. However, it was during the COVID-19 pandemic that this expansion solidified (Brazil, 2024). In the first year of the pandemic, the Federal Public Administration issued Normative Instruction Nº 65 on July 30, 2020, and later, Decree Nº 11,072 on May 17, 2022. These regulations established rules for the implementation of the Management and Performance Program (PGD) and provided guidance on telecommuting (Brazil, 2020e, 2022b). At the Federal University of São Carlos (UFSCar), telecommuting was initially implemented as an emergency measure in March 2020 to prevent the spread of the COVID-19 virus. Subsequently, on June 3, 2022, GR Ordinance Nº 5.684/2022 was approved, regulating the Management Program at UFSCar. According to university norms, it is the responsibility of each organizational unit’s leadership, in collaboration with their teams, to assess the feasibility of implementing the Management Program within their unit and determine the possible modes of work. Considering the role of leadership in this process, the overarching goal of this study is to identify the factors influencing managers’ decision-making regarding the adoption or non-adoption of telework for employees during the implementation of the Management Program at UFSCar. To conduct this study, a qualitative research approach was employed. The research is designed as a single-case study with a descriptive nature. Data were collected through documentary research, participant observation, and questionnaires. The questionnaire was administered to immediate supervisors in administrative and academic units at UFSCar, where employees are enrolled in the Management Program. The research aims to understand the decision-making process related to telecommuting adoption, with the results contributing to best practices in telecommuting management that enhance its continuity and effectiveness within UFSCar.